1993
DOI: 10.1007/bf02631364
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cell growth by bafilomycin A1, a selective inhibitor of vacuolar H+-ATPase

Abstract: Bafilomycin A1, a potent selective inhibitor of vacuolar H(+)-ATPase, inhibited the growth of a variety of cultured cells dose-dependently, including golden hamster embryo and NIH-3T3 fibroblasts, whether or not they were transformed, and PC12 and HeLa cells. The concentration of bafilomycin A1 for 50% inhibition of cell growth ranged from 10 to 50 nM. The dose response was nearly parallel with that of the bafilomycin A1-induced lysosomal pH increase. The degree of pH increase for growth inhibition produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 32 publications
4
50
1
Order By: Relevance
“…Experiments measuring the pH in cellular vesicles during treatment with acidification inhibitors have found that neither type of inhibitor raises the pH of endosomes to neutrality unless excessive concentrations are used, and the effectiveness of bafilomycin A1 and ammonium chloride in raising the pH was often not equivalent and can depend on cell type (37,42,67). We have shown that HMPV F protein-promoted fusion increases steadily as the pH to which the protein is exposed decreases (49).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments measuring the pH in cellular vesicles during treatment with acidification inhibitors have found that neither type of inhibitor raises the pH of endosomes to neutrality unless excessive concentrations are used, and the effectiveness of bafilomycin A1 and ammonium chloride in raising the pH was often not equivalent and can depend on cell type (37,42,67). We have shown that HMPV F protein-promoted fusion increases steadily as the pH to which the protein is exposed decreases (49).…”
Section: Discussionmentioning
confidence: 99%
“…the erythroid cell differentia-K. Kinoshita et al IFEBS Letters 337 (1994) [221][222][223][224][225] tion of Friend leukemia cells; unpublished observation), due to its growth inhibitory activity [29], should help us to elucidate the general cascade of information transmission in cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in close agreement with previous studies that have assessed the inhibition of VSV or MuLV-E by lysosomotropic agents (2,27,28,35). Experiments with BFLA1 were complicated by a toxic effect of the drug that inhibits cell growth (25,37). NIH 3T3 cell cultures treated with BFLA1 exhibited an initial lag in growth compared to untreated cells.…”
Section: Methodsmentioning
confidence: 99%